2022
DOI: 10.3390/microorganisms10030560
|View full text |Cite
|
Sign up to set email alerts
|

23-Valent Pneumococcal Polysaccharide Vaccination Does Not Prevent Community-Acquired Pneumonia Hospitalizations Due to Vaccine-Type Streptococcus pneumoniae

Abstract: Controversy exists regarding the clinical effectiveness of the 23-valent pneumococcal polysaccharide vaccine (PPSV23) for the prevention of serotype-specific community-acquired pneumonia (CAP). The objective of this study was to define the effectiveness of PPSV23 for the prevention of CAP hospitalizations due to vaccine-contained serotypes. This secondary analysis was a nested case–control, test-negative study design of adult patients hospitalized for CAP between 1 June 2014 and 31 March 2017. Cases included p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 15 publications
0
20
1
Order By: Relevance
“…PCV7, PCV10, and PCV13 have demonstrated robust protection against invasive and noninvasive disease including pneumonia, acute otitis media, and nasopharyngeal carriage among children; further, PCV13 protected against adult vaccine-type invasive disease and bacteremic and nonbacteremic pneumonia in an RCT in The Netherlands (10)(11)(12)(13). Although no RCT has directly compared the efficacy of PCV vaccines with that of PPSV23 in adult populations, one study in Louisville, KY, among persons aged 65 or older reported vaccine effectiveness of 71% for PCV13 against vaccine-type pneumonia (14), whereas a second study reported effectiveness of 17% for PPSV23 against pneumonia for PPSV23-unique serotypes (15). Similar paired data from Germany and the United States reported effectiveness against all-cause pneumonia in older adults of 12 and 8.8% for PCV13 compared with 3 and 1% for PPSV23 (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…PCV7, PCV10, and PCV13 have demonstrated robust protection against invasive and noninvasive disease including pneumonia, acute otitis media, and nasopharyngeal carriage among children; further, PCV13 protected against adult vaccine-type invasive disease and bacteremic and nonbacteremic pneumonia in an RCT in The Netherlands (10)(11)(12)(13). Although no RCT has directly compared the efficacy of PCV vaccines with that of PPSV23 in adult populations, one study in Louisville, KY, among persons aged 65 or older reported vaccine effectiveness of 71% for PCV13 against vaccine-type pneumonia (14), whereas a second study reported effectiveness of 17% for PPSV23 against pneumonia for PPSV23-unique serotypes (15). Similar paired data from Germany and the United States reported effectiveness against all-cause pneumonia in older adults of 12 and 8.8% for PCV13 compared with 3 and 1% for PPSV23 (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, PCV13 (pneumococcal conjugate vaccine) vaccination is recommended for infants 2 months to 2 years old, and those with immunosuppressive diseases under the age of 19 are also recommended to be vaccinated [ 32 ]. Adults above 65 years of age are recommended PPSV23 (Pneumococcal Polysaccharide Vaccine) to prevent themselves from acquiring CABP [ 33 ]. A major concern related to the treatment of patients with CABP include adverse effects as well as collateral damage to the microbiome with an associated risk of Clostridium difcile infection [ 34 , 35 ].…”
Section: Current Strategiesmentioning
confidence: 99%
“…18 Systematic reviews and meta-analyses support the efficacy of PPV23 against invasive pneumococcal disease (IPD); however, VE against non-bacteraemic pneumococcal pneumonia is uncertain. [19][20][21][22][23] The current consensus is that PPV23 does not offer protection against natural colonisation. 19 Effects in CHIMs have yet to be established.…”
Section: Pneumococcal Vaccinesmentioning
confidence: 99%
“…To compare the rate of acquisition of experimental SPN6B colonisation at EACH and ANY time point during the23 days following EHPC in persons 6 months post pneumococcal vaccination (PCV-13 or PPV-23) to controls defined by classical culture and molecular methods from NW. The rate of experimental SPN6B colonisation determined by the presence of experimental SPN6B in NW by classical culture and PCR (combined and individually) at EACH and ANY time point (D2, 7, 14, 23) following EHPC 6 months after vaccination in PCV-13 vs control and PPV-23 vs control.…”
mentioning
confidence: 99%